PENERAPAN ASESMEN PORTOFOLIO DENGAN MODEL PEMBELAJARAN BERBASIS PRODUKSI - Maddatuang, Jufrina (Parameter, 2015)
This research shows an learning alternative which is learning based on production with assesment portofolio approach. As qualitative give quality improvement and meaningful learning, especially learning experience which connecting a student with worforce or Works unit convenient with standar and field specification. On the other context result shows from process and learning product, in average get inclination that competences are assessed from performance portofolio which is student owned, and the last product form work unit get in good category. Some factor determinis a successful model application, such as: lecturer competencies, student readiness, tools avaibility and object avaibility suited construct specification and from Financial side.